2018
DOI: 10.1002/prp2.418
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, pharmacokinetics, and pharmacodynamics of mirogabalin in healthy subjects: Results from phase 1 studies

Abstract: Three phase 1 pharmacokinetic (PK)/pharmacodynamics (PD) studies were conducted in healthy men and women to further characterize the safety, tolerability, and PK/PD of mirogabalin administration with or without food and to guide the dose selection and regimen for phase 2 and 3 clinical development. The 3 studies included 2 randomized, double‐blind, placebo‐controlled, single‐ and multiple‐ascending‐dose studies, and 1 open‐label, crossover study to evaluate the PK of mirogabalin administered under fasting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
(29 reference statements)
3
23
1
1
Order By: Relevance
“…Pregabalin was selected as the active control since both agents target the same voltage-gated calcium channel a 2 d subunit, and because pregabalin is approved in many countries for the treatment of DPNP [13,15]. No upper age limit was placed on this study, since a phase 1 study in elderly subjects showed no Data are given as n (%) Adverse events were coded using the Medical Dictionary for Regulatory Activities version 16.0 BID twice daily, PT preferred term, SOC system organ class notable differences from the results obtained in non-elderly subjects with regard to safety, tolerability, and pharmacokinetics [33]. Nevertheless, despite these elements of study design, mirogabalin produced numeric but not statistically significant improvements compared with placebo, and almost no impact was observed with pregabalin on any measure, likely due to the subjective nature of pain measurement and the difficulty in minimizing the placebo response [34].…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin was selected as the active control since both agents target the same voltage-gated calcium channel a 2 d subunit, and because pregabalin is approved in many countries for the treatment of DPNP [13,15]. No upper age limit was placed on this study, since a phase 1 study in elderly subjects showed no Data are given as n (%) Adverse events were coded using the Medical Dictionary for Regulatory Activities version 16.0 BID twice daily, PT preferred term, SOC system organ class notable differences from the results obtained in non-elderly subjects with regard to safety, tolerability, and pharmacokinetics [33]. Nevertheless, despite these elements of study design, mirogabalin produced numeric but not statistically significant improvements compared with placebo, and almost no impact was observed with pregabalin on any measure, likely due to the subjective nature of pain measurement and the difficulty in minimizing the placebo response [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mirogabalin was tested in healthy volunteers at doses ranging from 3 to 75 mg [ 23 ]. After oral administration, mirogabalin is quickly absorbed, with a mean time to maximum plasma concentration (T max ) of 0.5–1.5 h after single or repeated doses [ 5 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…After oral administration, mirogabalin is quickly absorbed, with a mean time to maximum plasma concentration (T max ) of 0.5–1.5 h after single or repeated doses [ 5 ]. The plasma maximum concentration (C max ) and concentration–time curve (AUC) increased in a dose-dependent manner, whereas the steady-state plasma concentration was achieved by day 3 [ 23 ]. In the fed state, T max is delayed by 0.5 h after taking a 15 mg dose of mirogabalin, and C max is reduced by approximately 18%, but it does not influence its general exposure to any clinically relevant degree [ 23 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Fed (high-fat meal) or fasting states in healthy volunteers did not affect bioavailability after taking a single dose of mirogabalin 15 mg. No food restriction was needed when taking mirogabalin in a phase 1 study [44].…”
Section: (8) Bioavailability To Food Intakementioning
confidence: 99%